2009
DOI: 10.1556/avet.57.2009.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Spaying-related urinary incontinence and oestrogen therapy in the bitch

Abstract: Some aspects of spaying-related urinary incontinence in the bitch still remain incompletely clarified. Therefore, the aims of the present study were to evaluate the prevalence of the disease among spayed dogs, to detect differences in risk related to the type of surgery, to describe the characteristics of incontinent bitches, to assess the influence of age at surgery on the onset of incontinence occurrence, and to assess the effectiveness and long-term side effects of oestrogen therapy in affected bitches. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
2
16
0
3
Order By: Relevance
“…Urinary incontinence typically develops 3 to 5 years after gonadectomy. [129][130][131][132] It affects 2% to 20% of spayed females and occurs most often in larger dogs. [129][130][131][132] Females spayed before 3 months of age have the highest risk of developing urinary incontinence that requires medical treatment.…”
Section: Other Medical Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Urinary incontinence typically develops 3 to 5 years after gonadectomy. [129][130][131][132] It affects 2% to 20% of spayed females and occurs most often in larger dogs. [129][130][131][132] Females spayed before 3 months of age have the highest risk of developing urinary incontinence that requires medical treatment.…”
Section: Other Medical Implicationsmentioning
confidence: 99%
“…[129][130][131][132] It affects 2% to 20% of spayed females and occurs most often in larger dogs. [129][130][131][132] Females spayed before 3 months of age have the highest risk of developing urinary incontinence that requires medical treatment. 4,131 Spaying females between 4 and 6 months of age does not appear to increase the risk for urinary incontinence, compared with the risk for those spayed after the first estrus.…”
Section: Other Medical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…1% of intact bitches (Holt and Thrusfield 1993), but incontinence rates after spaying have been reported as being between 3. 1% and 20% (von Ruckstuhl 1978;Arnold et al 1989;Holt and Thrusfield 1993;Okkens, Kooistra and Nickel 1997;Angioletti et al 2004;Veronezi et al 2009). Thrusfield, Holt and Muirhead (1998) reported that neutered bitches have a 7.8-fold greater risk of developing urinary incontinence compared with entire bitches.…”
Section: Bitchesmentioning
confidence: 99%